Pregnancy in a noncommunicating rudimentary horn of a unicornuate uterus: Prerupture diagnosis and management - Yu-Ju Lai; Chen-Hsien Lin; Wen-Chien Hou; Kwei-Shuai Hwang; Mu-Hsien Yu; Her-Young Su (Elsevier, 2016)
Objective: The estimated incidence of rudimentary horn pregnancy is one in 76,000. It is a life-threatening entity with a 50% risk of uterine rupture. With advances in prenatal ultrasound in recent decades, there may be an opportunity to detect rudimentary horn pregnancy earlier, resulting in a lower incidence of maternal morbidity and mortality. Management is typically resection of the rudimentary horn and the ipsilateral fallopian tube by either laparotomy or laparoscopy. Case Report: Here, we present the case of a 22-year-old woman with a suspected ectopic pregnancy of 12 weeks' gestation. Ultrasound and magnetic resonance imaging were performed as preoperative evaluations. A definitive diagnosis was made during laparotomy, and resection of the rudimentary horn pregnancy was performed. Conclusion: Diagnosis and management of rudimentary horn pregnancy remain a challenge. We should be alert to prenatal ultrasound with the intention of making an earlier diagnosis, thereby resulting in decreased maternal morbidity and mortality.